2014
DOI: 10.1080/10615806.2013.876010
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in adolescent coping behaviors and suicidal ideation: findings from a sample of 73,238 adolescents

Abstract: Suicide among adolescents is an emerging global public health problem as well as a socioeconomic problem. Stress-coping strategies have been shown to be associated with suicidal ideation. We examined coping behaviors related to suicidal ideation and gender differences in adolescents using the data from the 2010 Korea Youth Risk Behavior Survey (ages 12-19 years; N = 73,238). Logistic regression analysis was used to evaluate associations between suicidal ideation and specific coping behaviors while controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
(55 reference statements)
2
19
0
Order By: Relevance
“…Substances used for coping, such as drinking alcoholic beverages and smoking cigarettes, are positively associated with suicidal ideation and attempts in both male and female adolescents, as well as adults. 38 39 Therefore, developing adaptive coping strategies in female youths other than smoking is important in order to reduce initiation of smoking. In addition, proper evaluation and management of mental health problems among female current smokers may lead to smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Substances used for coping, such as drinking alcoholic beverages and smoking cigarettes, are positively associated with suicidal ideation and attempts in both male and female adolescents, as well as adults. 38 39 Therefore, developing adaptive coping strategies in female youths other than smoking is important in order to reduce initiation of smoking. In addition, proper evaluation and management of mental health problems among female current smokers may lead to smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide ideation also is associated with how well individuals are able to cope with stress [ 23 – 26 ]. For example, findings from concurrent studies indicate that individuals with higher levels of suicide ideation engage in more frequent (calculated by a means-based approach) maladaptive coping strategies [ 23 , 25 ] and tend to have more trouble problem solving in the face of stress [ 27 ], compared to individuals with lower levels of suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators found that there were gender differences in the effects of various demographic and risk factors for suicidal ideation. [34][35][36] Indeed, in Model 3, which was adjusted for age, BMI, smoking, drinking, exercise, education, income, metabolic syndrome, DM and HTN, suicidal ideation was correlated with lower BMD in males. Suicidal ideation could be the cumulative product of various mental health problems, although stress and depressed mood were relatively singular and homogenous expressions of mental health problems.…”
Section: Discussionmentioning
confidence: 98%